Vitamin D and Relationship with Cholesterol and Triglycerides - Albakour, Emad Jamil; Eljamay, Salwa Muftah; Faid, Fathia Eessa; Ibrahim, Najah Ahmeda (Indonesian Journal of Community Services, 2025)
The study focuses on cholesterol and triglycerides. Vitamin D has a relationship with lipid profile. Material and Methods: involved 2,188 participants, equally divided between males and females, with a wide age distribution. Vitamin D levels were assessed using serum 25-hydroxyvitamin D (25(OH)D) concentration. The findings: The correlation analysis reveals no significant relationships between Vitamin D levels and the variables of age, gender, cholesterol, and triglycerides. All correlation coefficients are near zero, and the p-values exceed the standard significance threshold (0.05), indicating statistical insignificance. Specifically: Age: No meaningful variation in Vitamin D levels with age (P = 0.903). Gender: No substantial difference between males and females (P-value = 0.192). Cholesterol: No significant association with Vitamin D levels (P-value = 0.851). Triglycerides: No meaningful relationship observed (P-value = 0.699). Conclusion: The correlation analysis confirmed no meaningful associations between Vitamin D levels and age, gender, cholesterol, or triglyceride levels. All correlation coefficients were near zero, and p-values exceeded the standard significance threshold (0.05), indicating no statistically significant relationships.